Unexpected Macrocyclic Multinuclear Zinc and Nickel Complexes that Function as Multitasking Catalysts for CO2 Fixations. Issue 29 (7th June 2019) - Takaishi, Kazuto; Nath, Bikash Dev; Yamada, Yuya; Kosugi, Hiroyasu; Ema, Tadashi
Abstract: Unique self‐assembled macrocyclic multinuclear Zn II and Ni II complexes with binaphthyl‐bipyridyl ligands (L) were synthesized. X‐ray analysis revealed that these complexes consisted of an outer ring (Zn3 L3 or Ni3 L3 ) and an inner core (Zn2 or Ni). In the Zn II complex, the inner Zn2 part rotated rapidly inside the outer ring in solution on an NMR timescale. These complexes exhibited dual catalytic activities for CO2 fixations: synthesis of cyclic carbonates from epoxides and CO2 and temperature‐switched N ‐formylation/ N ‐methylation of amines with CO2 and hydrosilane. Abstract : Multi‐task catalysts : Unique self‐assembled macrocyclic multinuclear Zn II and Ni II complexes with binaphthyl–bipyridyl ligands (L) were synthesized. These complexes consisted of an outer ring (Zn3 L3 or Ni3 L3 ) and an inner core (Zn2 or Ni). These complexes acted as multitask catalysts for CO2 fixations.